2007
DOI: 10.1016/j.cub.2007.05.039
|View full text |Cite
|
Sign up to set email alerts
|

clockwork orange Encodes a Transcriptional Repressor Important for Circadian-Clock Amplitude in Drosophila

Abstract: Gene transcription is a central timekeeping process in animal clocks. In Drosophila, the basic helix-loop helix (bHLH)-PAS transcription-factor heterodimer, CLOCK/CYCLE (CLK/CYC), transcriptionally activates the clock components period (per), timeless (tim), Par domain protein 1 (Pdp1), and vrille (vri), which feed back and regulate distinct features of CLK/CYC function. Microarray studies have identified numerous rhythmically expressed transcripts, some of which are potential direct CLK targets. Here we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
122
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 38 publications
11
122
1
4
Order By: Relevance
“…3). Moreover, previous studies showed that two copies of Cwo producing overexpression by tim-Gal4 (tim-Gal4/ þ ; UAS-cwo) generate a modest reduction of rhythmic power [12][13][14][15] , which can mimic the let-7 loss-of -function phenotype in this study, indicating that the let-7 mutant phenotype may be due to increased CWO expression. On the contrary, our results show that let-7 overexpression in Cwo cells lengthened circadian period, which is consistent with the effect of cwo-RNAi in both Cwo cells and Tim cells, and it was able to be partially rescued by Cwo overexpression, indicating regulation of Cwo by let-7.…”
Section: =2498±004 H Pdf-gal4/+;uas-let-7/+supporting
confidence: 65%
See 3 more Smart Citations
“…3). Moreover, previous studies showed that two copies of Cwo producing overexpression by tim-Gal4 (tim-Gal4/ þ ; UAS-cwo) generate a modest reduction of rhythmic power [12][13][14][15] , which can mimic the let-7 loss-of -function phenotype in this study, indicating that the let-7 mutant phenotype may be due to increased CWO expression. On the contrary, our results show that let-7 overexpression in Cwo cells lengthened circadian period, which is consistent with the effect of cwo-RNAi in both Cwo cells and Tim cells, and it was able to be partially rescued by Cwo overexpression, indicating regulation of Cwo by let-7.…”
Section: =2498±004 H Pdf-gal4/+;uas-let-7/+supporting
confidence: 65%
“…CLK-CYC also activates two other feedback loops critical for the phase and amplitude of core oscillators and outputs. One feedback loop affecting Clk mRNA cycling is mediated by VRILLE (VRI) and PAR DOMAIN PROTEIN 1 expression 10,11 , and another is mediated by CLOCKWORK ORANGE (CWO), which is activated by CLK-CYC [12][13][14][15] . The per and tim genes receive two opposing signals form DNA-binding transcription factors-a direct activation from CLK-CYC and a direct repression from CWO.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, the master genes Clock (Clk) and cycle (cyc) activate the circadian system by promoting rhythmic transcription of a number of key genes [2][3][4] . Three of these target gene products, PERIOD (PER) 5 , TIMELESS (TIM) 6 and CLOCKWORK ORANGE (CWO) [7][8][9] , repress CLK-CYC-mediated transcription on a daily basis. CLK activates transcription only while associated with CYC.…”
mentioning
confidence: 99%